Geographic variation of mutagenic exposures in kidney cancer genomes - Senkin, Sergey; Moody, Sarah; Díaz-Gay, Marcos; Abedi-Ardekani, Behnoush; Cattiaux, Thomas; Ferreiro-Iglesias, Aida; Wang, Jingwei; Fitzgerald, Stephen; Kazachkova, Mariya; Vangara, Raviteja; Le, Anh Phuong; Bergstrom, Erik N; et al. (Nature, 2024)
International differences in the incidence of many cancer types indicate the existence of carcinogen exposures that have not yet been identified by conventional epidemiology make a substantial contribution to cancer burden1. In clear cell renal cell carcinoma, obesity, hypertension and tobacco smoking are risk factors, but they do not explain the geographical variation in its incidence2. Underlying causes can be inferred by sequencing the genomes of cancers from populations with different incidence rates and detecting differences in patterns of somatic mutations. Here we sequenced 962 clear cell renal cell carcinomas from 11 countries with varying incidence. The somatic mutation profiles differed between countries. In Romania, Serbia and Thailand, mutational signatures characteristic of aristolochic acid compounds were present in most cases, but these were rare elsewhere. In Japan, a mutational signature of unknown cause was found in more than 70% of cases but in less than 2% elsewhere. A further mutational signature of unknown cause was ubiquitous but exhibited higher mutation loads in countries with higher incidence rates of kidney cancer. Known signatures of tobacco smoking correlated with tobacco consumption, but no signature was associated with obesity or hypertension, suggesting that non-mutagenic mechanisms of action underlie these risk factors. The results of this study indicate the existence of multiple, geographically variable, mutagenic exposures that potentially affect tens of millions of people and illustrate the opportunities for new insights into cancer causation through large-scale global cancer genomics.
Keywords: nádory ledvin; Serbia; Male; hypertenze; mutace; Tobacco Smoking; zeměpis; Japan; Obesity; Risk Factors; genom lidský; Romania; karcinom z renálních buněk; Thailand; obezita; Kidney Neoplasms; Srbsko; Thajsko; mužské pohlaví; Rumunsko; incidence; Genomics; Hypertension; Geography; Mutagens; Aristolochic Acids; Genome, Human; kyseliny aristolochové; mutageny; lidé; ženské pohlaví; Humans; Japonsko; rizikové faktory; Environmental Exposure; Carcinoma, Renal Cell; Mutation; Female; Incidence; kouření tabáku; vystavení vlivu životního prostředí; genomika